Chronic psychological trauma predicts mental and physical trauma symptoms differentially based on gender and levels of resilience and forgiveness - Jeter, Whitney Kristin (Kansas State University, 2013)
A large majority of trauma research focuses on relatively acute, physical trauma leading to the development of negative mental and physical trauma symptoms. Sometimes psychological trauma is measured concurrently with these instances of physical trauma. However, less is known about the impact of solely psychological trauma on mental and physical trauma symptom development. Moreover, chronic rather than acute psychological trauma is even more understudied. Therefore, the purpose of the current study was to address the gap of knowledge surrounding the impact of chronic psychological trauma on mental and physical health in young adults. The present inquiry was guided by two theoretical models: the Chronic Relational Trauma (CRT) Model and the Etiology of Psychopathology (EP) Model. The CRT Model posits a cyclical pattern of relational trauma perpetrated by caregivers, peers, and intimate partners. Relatedly, the EP Model focuses on acute physical trauma exposure leading to the development of negative mental and physical trauma symptoms as well as potential biological dysregulation with personality characteristics moderating these relationships. However, it is currently unknown how these moderating personality characteristics impact chronic psychological trauma. Thus, the current study blended these two theoretical models in order to examine the impact of chronic psychological trauma on mental, physical, and biological symptoms. One hundred and eighty young adults (Mean age = 18.53, SD = .70) were recruited for the current study. Participants completed a series of questionnaires and provided five total cortisol samples via oral swabs. Results indicate that after controlling for chronic physical trauma, chronic psychological trauma predicts mental trauma symptoms for females and males, but not physical trauma symptoms or biological dysregulation in cortisol. Further, levels of resilience, namely a sense of mastery and emotional reactivity as well as forgiveness significantly moderate the relationship between chronic psychological trauma and mental and physical trauma symptoms for males and females differentially. Contributions of the current findings in terms of adding unique knowledge to trauma literature and future research projects are discussed.
Keywords: Trauma; Resilience; Forgiveness; Gender; Personality Psychology (0625)